2010
DOI: 10.1126/science.1184334
|View full text |Cite
|
Sign up to set email alerts
|

Channel-Mediated Tonic GABA Release from Glia

Abstract: Synaptic inhibition is based on both tonic and phasic release of the inhibitory transmitter γ-aminobutyric acid (GABA). Although phasic GABA release arises from Ca(2+)-dependent exocytosis from neurons, the mechanism of tonic GABA release is unclear. Here we report that tonic inhibition in the cerebellum is due to GABA being released from glial cells by permeation through the Bestrophin 1 (Best1) anion channel. We demonstrate that GABA directly permeates through Best1 to yield GABA release and that tonic inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
532
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 491 publications
(565 citation statements)
references
References 45 publications
30
532
3
Order By: Relevance
“…Hence, GABA A receptors can generate two types of current, depending on their location and subunit composition: the first type is the classic synaptic phasic (or 'transient') current that results from the release of GABA from synaptic vesicles in the synaptic cleft; the second type is a tonic ('always on') current that is caused by GABA A receptors responding to low levels of ambient GABA (Farrant and Nusser, 2005). Recently, it has been demonstrated that GABA leading to tonic activation of GABA A receptors is released, at least in cerebellum, from glial cells by permeation through bestropin 1 anion channels (Lee et al, 2010). It has also been reported that taurine can activate extrasynaptic GABA A receptors in the mouse ventrobasal thalamus thus reducing the excitability of thalamocortical relay neurons (Jia et al, 2008).…”
Section: Gaba a Receptor-mediated Tonic Inhibitionmentioning
confidence: 99%
“…Hence, GABA A receptors can generate two types of current, depending on their location and subunit composition: the first type is the classic synaptic phasic (or 'transient') current that results from the release of GABA from synaptic vesicles in the synaptic cleft; the second type is a tonic ('always on') current that is caused by GABA A receptors responding to low levels of ambient GABA (Farrant and Nusser, 2005). Recently, it has been demonstrated that GABA leading to tonic activation of GABA A receptors is released, at least in cerebellum, from glial cells by permeation through bestropin 1 anion channels (Lee et al, 2010). It has also been reported that taurine can activate extrasynaptic GABA A receptors in the mouse ventrobasal thalamus thus reducing the excitability of thalamocortical relay neurons (Jia et al, 2008).…”
Section: Gaba a Receptor-mediated Tonic Inhibitionmentioning
confidence: 99%
“…GABA acts at inhibitory synapses in the brain by binding to specific receptors in pre- and post-synaptic neurons. Recent studies have demonstrated a robust release of GABA from glial cells in human astrocytes and acute brain slices [18,41]. Furthermore, astrocytic release of GABA can cause tonic inhibition in several brain regions, including the thalamus and cerebellum [42,43].…”
Section: Cnts Modulate the Intracellular Distribution Of Gaba In Astrmentioning
confidence: 99%
“…Tonic inhibition orginates from the sustained activation of high affinity GABA receptors by ambient GABA [22]. In the cerebellum, some studies have reported that a Ca 2+ -activated anion channel, Best1, mediates tonic inhibition by releasing GABA through direct permeation [18,43]. In addition, glial MAOB is a key synthesizing enzyme of GABA and converts putrescine to GABA in the mitochondria of astrocytes [44].…”
Section: Cnts Modulate the Intracellular Distribution Of Gaba In Astrmentioning
confidence: 99%
See 2 more Smart Citations